Dietary Maize Starch Influences Growth Performance, Apparent Digestibility Coefficient, and Hepatic Enzyme Activities of Carbohydrate Metabolism in Obscure Puffer, Takifugu obscurus (Abe). Issue 1 (February 2015) - Liu, Xiang‐He; Ye, Chao‐Xia; Zheng, Li‐Mian; Ou, Cheng‐Cheng; Wang, An‐Li; Ye, Ji‐Dan; Kong, Jiang‐Hong
Abstract A 60‐d feeding trial was conducted to investigate the effect of dietary maize starch on growth performance, feed utilization, and apparent digestibility coefficient (ADC) and key hepatic enzyme activities regulating glycolytic and gluconeogenic metabolic pathways of juvenile obscure puffer, Takifugu obscurus (Abe) (initial body weight = 7.9 ± 0.2 g). Five isonitrogenous and isolipidic diets containing graded levels of maize starch (10, 15, 20, 25, and 30%) were formulated. Results demonstrated that weight gain (WG), specific growth rate (SGR), protein efficiency ratio (PER), protein productive value (PPV), and energy productive value (EPV) increased with increasing dietary maize starch up to 25% (P < 0.05), and thereafter WG, SGR, PER, PPV, and EPV declined. Hepatosomatic index and viscerosomatic index, plasma glucose, triglycerides, and liver glycogen and liver lipid concentration of fish significantly increased with increasing dietary maize starch level (P<0.05). ADC of starch reduced significantly up to 25%, while ADC of dry matter showed a contrary tendency. However, survival, whole body and muscle compositions, and ADCs of protein and lipid showed no significant differences. Dietary maize starch supplements tended to enhance gluconokinase and pyruvate kinase activities of the liver, but no significant differences were observed in activities of hexokinase, phosphofructokinase‐1, fructose‐1, 6‐bisphosphatase, and glucose‐6‐phosphatase in the liver among dietary treatments. Based on WG and FCR, the appropriate dietary maize starch supplementations of juvenile obscure puffer were estimated to be 23.5 and 22.5% of diet, respectively.